Sistem Pendukung Keputusan Kelompok Promosi Jabatan Menggunakan Metode Profile Matching - Sugiartawan, Putu; Ardriani, Ni Nengah Dita; Kusuma, I Made Wijaya (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2021)
The important thing in supporting the progress and quality of an organization in achieving its goals is quality human resources. Warrant the right person in a certain position, and employee selection has always been a very important part of the organization. STMIK STIKOM Indonesia is an educational institution that focuses on computer-based science education. This institution has problems, such as the difficulty of determining the right person to occupy certain positions. Promotions are only judged based on several criteria, such as length of service, discipline, work performance, and less transparent promotions. The promotion process can be completed with a decision support system to calculate the consideration of each competency possessed by each candidate. The method used is profile matching. This method first determines the competence (ability) required by a position. Then the profile matching method is combined with the Borda method to complete group decision-making based on the voting of each decision-maker (DM). The aspects used, namely parts of intelligence, work attitudes, and behavior, are divided into several sub-criteria. The results of this study are in the form of a ranking report with a broad approach based on the results of profile matching calculations, which is expected with this system to facilitate the implementation of regeneration and career paths in campus organizations.